Influência dos parâmetros urbanos e da topografia para a disponibilidade de luz natural em edifícios residenciais em Belo Horizonte - Cláudia Rocha Guidi (2018)
The purpose of the present study was to evaluate the influence of the urban parameters correlated to terrain slope over the daylight admission in bedrooms and living rooms of a residential building located in Belo Horizonte from representative urban tissues of the topographic mesh as well as typologies of residential buildings typically found em the city. The analysis addressed the slope, the vertical location of the unit in 4 geographic orientations. The evaluations were carried out according to NBR 15.575 (ABNT, 2013a) and to RTQ-R (BRASIL 2012). requirements using NBR 15.215 parts 2 and 3 (2005b; 2005c) and computer simulation. For the NBR 15.575 alternative simulation methods were also studied using the requirements of the standard. It was run 160 computer simulations in the software Daysim. It was verified that longitudinal terrain slope and the unit vertical location have a significant influence on indoor daylight and also verified that NBR 15.575 requirements are more permissive than RTQ-R requirements. Using NBR 15.575 graphic methods all illuminances were within the minimum values. Using computer simulation, the average percentage of service was between 52 to 62% and in steeper terrain slope, the percentage was 25 to 44%. Correlating the first floor with the steeper terrain slope, no one room did not meet the requirements of the standard. The results showed that 28% of the rooms in one of the urban tissues meet the RTQ-R bônus requirements and the values of the other urban tissues was 46%. In the steeper terrain slope, the values of percentage of service were 11 to 31%. In the first floor, only 2,5% of the rooms meet the requirements, independently of the terrain slope. These results showed that longitudinal terrain slope and built environment have significant influence on indoor daylight wich indicated that the city urban legislation should be revised including the analysis of these variables.